Os usos sociais do corpo na 'praia carioca do Pepê' - Braga, Marcelo Fernando Leite (2010)
When the field is the 'Rio Beach of Pepê' and the 'Social Uses of the Body' in the form of 'distinction' in relation to social classes in the construction of the aesthetic disposition with regard to taste, consumption, lifestyle and class habits. Through this 'field study', I tried to capture the representations that individuals make of their bodies in the ' Rio Beach of Pepê ' to confront the reality presented to me on that beach space investigated. With that sought to establish whether there is a social imaginary of the 'body' and how this imagery appears in this space from the beach.